Trabecular tumour of the Thyroid: adenoma or papillary carcinoma? A clinical case report - Ponte, Alcina (2002)
The authors describe a case of a young woman with a thyroid mass. Fine needle aspiration of the thyroid revealed a Hürthle cell tumour. Histologic diagnosis was papillar carcinoma – trabecular variant. Hyalinizing trabecular adenoma (HTA) is a follicle-derived tumour of the thyroid gland and has been described as benign. Currently, discussions are underway to decide whether or not HTA should be regarded as a trabecular form of the encapsulated variant of papillar carcinoma.